PENETAPAN TINGKAT KEPENTINGAN DAN KEPUASAN KONSUMEN TERHADAP BERAS ANALOG BERBASIS JAGUNG - Astuti, Santi Dwi; Caecar, Desinta Afifah; Dewi, Ervina Mela; Novitasari, Dian (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
Corn-based analog rice is one of the new products developed by PT. HDN. Analog rice is a local food innovation made from corn and cassava ingredients that is presented as a healthy food alternative with a low glycemic index and high fiber. This research aims to determine consumer acceptance of the product. Data collection from respondents was conducted by distributing questionnaires to 100 respondents who met the criteria. The data obtained were analyzed using the Importance-Performance analysis and Customer Satisfaction Index methods. The aspects studied include product, packaging, price & promotion. The attributes that are the main priorities are the aroma of rice, the aroma of cooked rice, the taste of cooked rice, the ease of opening and resealing the packaging, the presence of online promotions, and the ease of obtaining the product offline. The CSI result obtained was 75.82%, indicating that the level of consumer satisfaction with the corn analog rice product falls into the "satisfied" category.